Religious values and business angel investment decision-making: The influence of the Jewish ethos Tikkun Olam - Ethel Berdugo; Gilberto Sarfati (Internext: Revista Eletrônica de Negócios Internacionais)
Objectives: This study investigates the role of religious values in the investment decision-making process of Jewish business angels (BAs), highlighting how the Jewish ethos Tikkun Olam influences their behavior. The concept provides a motivational and attitudinal orientation that guides their investment choices. Method: To explore Tikkun Olam's influence, the research conducted in-depth interviews with 15 Jewish BAs of different nationalities (France, Brazil, and Israel). The sample size was determined based on the concept of theoretical saturation, ensuring that no new themes emerged after the 15 interviews. The interviews were analyzed using thematic analysis to identify dimensions related to Tikkun Olam in the respondents' narratives. Main results: The thematic analysis identified five main themes reflecting the influence of Tikkun Olam on the decision-making process of BAs. The first theme, "Collective Cohesion," showed that the respondents demonstrated a strong sense of responsibility toward their community, contributing through economic initiatives or altruistic help. The second theme, "Ethical Guidelines," highlighted how the pursuit of morality and consistency with personal and religious values guided investors to invest in ventures with a positive social impact. The third theme, "Improving the World," emphasized the investors' concern with social justice and environmental sustainability, driving them to seek companies that contribute to a better future. The fourth theme, "Never-Ending Search for Perfection," revealed a future-oriented mindset that encouraged investors to innovate and pursue changes that would improve the world. Finally, the fifth theme, "Belief in a Mystical Purpose," showed how belief in a higher power motivated investors to act with purpose, often basing their decisions on intuition and "gut feeling." Relevance / Originality and Theoretical Contributions: This study highlights how religious values shape BAs' decision-making, providing insights into how moral and religious elements influence high-risk investments. It also contributes to the literature by examining non-rational decision-making mechanisms, such as passion and intuition, and explores whether Jewish BAs exhibit distinct behaviors compared to non-religious BAs. The study proposes a conceptual framework that classifies the motivational and attitudinal orientations of investors based on Tikkun Olam. Managerial Contributions: Understanding moral biases allows BAs to refine their decision-making processes. Additionally, the study provides entrepreneurs with insights into the criteria that BAs use, facilitating better alignment between expectations and values.